FORMULASI CAMPURAN LIMBAH IKAN DAN IKAN RUCAH TERHADAP KANDUNGAN DAN DAYA CERNA PROTEIN TEPUNG IKAN - Helmi Haris; Ikromatun Nafsiyah (Balai Riset dan Standardisasi Industri Ambon, 2019)
Most of the waste produced by traditional food processing in Palembang has not been optimally utilized. Even if the waste is processed again, one of the things that can be produced is Fish Flour as raw material for making animal feed or fish feed. The way to process it is to do raw material translation, sorting and washing of raw materials, then steaming with presto tools, and reducing the size of raw materials to make it easier to process and break down the lumps found in the raw material. After that pressing is done and dried. After drying, the waste is pressed and weighed again and then packed to avoid contamination from the outside. The treatment of mixed formulations between fish and trash fish by side catches (HTS) significantly affected the protein content of fish meal, but did not significantly affect the digestibility of the protein. Protein content of fish meal in a row from the highest is found in treatment P6 (100% trash fish) and the lowest is in P1 (100% fish waste). Based on the protein content, the level of treatment P1 (100% fish waste) and P2 (80% fish waste: 20% trash fish) have not fulfilled the SNI for fish meal, but the level of treatment P3 (60% fish waste: 40% trash fish) and P4 ( fish waste 40%: trash fish 60%) have met III quality standards and the level of treatment P5 (20% fish waste: 80% trash fish) and P6 (100% trash fish) have met II quality standards based on SNI for fish meal.